1996
DOI: 10.1530/eje.0.1340337
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic application of thyrostatic drugs during excessive iodine exposure in euthyroid patients with thyroid autonomy: a randomized study

Abstract: In a prospective, randomized study we examined the influence of prophylactic short-term thyrostatic therapy on thyroid iodine metabolism in patients with euthyroid autonomy undergoing elective coronary angiography. From a total of 1177 patients, 51 fulfilled the criteria of euthyroid autonomy before coronary angiography (negative thyrotropin-releasing hormone test, 10-min uptake of at least 1.2%, 99mTc and no elevation of free thyroxine and free triiodothyronine indices) and were randomized into three groups: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
2
2

Year Published

1999
1999
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(33 citation statements)
references
References 11 publications
0
29
2
2
Order By: Relevance
“…Based on our observations, we do not support preventive measures as recommended by others (18). The study of Nolte et al (18) even shows that iodine-induced hyperthyroidism cannot be prevented by prophylactic therapy in every case.…”
Section: Discussioncontrasting
confidence: 84%
See 2 more Smart Citations
“…Based on our observations, we do not support preventive measures as recommended by others (18). The study of Nolte et al (18) even shows that iodine-induced hyperthyroidism cannot be prevented by prophylactic therapy in every case.…”
Section: Discussioncontrasting
confidence: 84%
“…Based on our observations, we do not support preventive measures as recommended by others (18). The study of Nolte et al (18) even shows that iodine-induced hyperthyroidism cannot be prevented by prophylactic therapy in every case. At this point it should be mentioned that the risk for side-effects of carbimazole (leukopenia 0.4%, thrombocytopenia 0.2%, agranulocytosis 0.2%) (19) is even higher than the risk of iodine-induced hyperthyroidism.…”
Section: Discussioncontrasting
confidence: 84%
See 1 more Smart Citation
“…These collective data bear great clinical relevance given the known adverse effects of hyperthyroidism on multiple organ systems (i.e., bone, neuropsychiatric) 16 particularly the cardiovascular system (e.g., atrial fibrillation, high-output heart failure, angina, and possibly greater cardiovascular mortality). 17,18 Although untested, it has been suggested that prophylactic treatment with methimazole or perchlorate may be warranted in high-risk patients in advance of anticipated iodide exposure such as elective ICM-based procedures; 2,19,20 further studies are needed to evaluate the safety and effectiveness of this approach.…”
Section: Discussionmentioning
confidence: 99%
“…In one prospective, randomized study of 1177 patients undergoing elective coronary angiography, 51 patients with euthyroid autonomy (i.e., suppressed TSH but normal thyroid hormone levels, negative thyrotropin-releasing hormone test and normal thyroidal radioisotope uptake study) identified as at increased risk of iodine-induced hyperthyroidism were randomly assigned to prophylactic treatment with perchlorate or thiamazole, or no treatment. 7 Hyperthyroidism developed in 2 patients in the control group and 1 in each of the treatment groups. The authors concluded that short-term prophylactic thyrostatic therapy appeared to have a protective effect against iodine excess in patients with euthyroid autonomy.…”
Section: Preventionmentioning
confidence: 98%